Desain Game Edukasi Ilmu Tajwid Bagi Anak Usia Dini menggunakan Pemodelan Finite State Automata - Yanto Yanto; Dinar Ismunandar; Erni Erni; Santoso Setiawan; Muhammad Ifan Rifani Ihsan (Universitas Hamzanwadi, 2021)
This study discusses how Finite State Automata (FSA) can be used as a model to design a Tajweed Science game application as a business diagram. This study aims to facilitate early childhood in learning the science of recitation by grouping hijaiyah letters into grouping the science of recitation by using a touch of the hand. The type of automata theory used is a non-deterministic finite automata with epsilon transition (E) or better known as E-NFA. Each transition, input, state that exists from the NFA, is basically to show the characteristics or states that occur in a game application. The importance of this research, in addition to learning recitation from an early age, is to show that automata theory can be used to help design a system in making game applications. The results of this Tajweed Science game application design are a rough display because there will still be further development stages and can ensure that game applications can be built from E-NFA modeling.